Edible Insects as Innovative Foods Nutritional, Functional and Acceptability Assessments - Jung, Chuleui; Meyer-Rochow, Victor Benno (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
There is global interest in using insects as food and feed. However, before insects can be recommended as a type of nourishment to augment more traditional and widely accepted sources of food and feed, it is essential that in-depth research involving a variety of subjects is carried out. We can learn from societies in which insects are still a component of the local diet which species are preferred and how they are prepared for human consumption. We need information on the chemical composition of edible insects and have to make sure we know what kinds of micro-organisms and pathogens they contain. Legal questions in relation to the sale and breeding of certain species need to be addressed, and medicinal aspects of edible insects and their products should be examined. How best to market selected species and make them palatable to a clientele that more than often rejects the idea of insects in the diet are further important aspects in need of study. This book deals with these questions in 19 articles written by experts from at least 20 different countries that represent a range of disciplines. As such, it is a useful tome for a wide range of food researchers.